Relationship-Specific Assets and the Pricing of Underwriter Services. - James, Christopher (Journal of Finance, 1992)
This paper investigates the effect of setup costs on the pricing of investment banking services. The existence of setup costs is predicted to result in lower underwriter spreads in initial public offerings for firms that are expected to issue again. Consistent with this prediction, the author finds significantly lower spreads for firms that make subsequent issues. He also finds that a firm's likelihood of changing underwriters in a subsequent offer is related to the time between offerings and the underwriter's pricing performance in the initial public offerings. These results suggest that the deviations from optimal initial public offerings pricing carry a penalty for the underwriter.